2018
DOI: 10.1039/c8ra04098b
|View full text |Cite
|
Sign up to set email alerts
|

Alpinumisoflavone attenuates lipopolysaccharide-induced acute lung injury by regulating the effects of anti-oxidation and anti-inflammation both in vitro and in vivo

Abstract: The present study demonstrated that alpinumisoflavone exerts the significant effects of anti-inflammatory and anti-oxidative in both LPS-induced RAW264.7 macrophages and a mouse model of acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The dose of hispolon was selected according to a previous study. After 6 h, the animals were sacrificed and samples were collected [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of hispolon was selected according to a previous study. After 6 h, the animals were sacrificed and samples were collected [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dose of hispolon was selected according to a previous study. After 6 h, the animals were sacrificed and samples were collected [31]. neutrophils and edema in the interstitial space of the alveolar wall were observed in the LPS group, indicative of alveolar epithelial cell damage.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpinumisoflavone (AIF) is a pyranoisoflavone isoflavone, and one of the major bioactive ingredient derived from the unripe fruits of C. tricuspidata [3,4,5,6]. AIF exhibits numerous beneficial pharmacological activities such as osteoprotective [7], antibacterial [8], estrogenic [9], anti-metastatic [10], atheroprotective [11], and antioxidant [12] effects. Moreover, considerable evidence has shown that AIF possesses in vitro and in vivo anticancer activities [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…Namkoong et al revealed that AIF suppressed the nuclear factor (NF)-κB pathway and extracellular signal-regulated kinases (ERKs)/mitogen-activated protein kinase (MAPK) and induced apoptosis of lung cancer cells [3]. AIF is also known to attenuate lipopolysaccharide-induced acute lung injury by regulating the effects of antioxidation and anti-inflammation both in vitro and in vivo [12]. Gao et al [4] found that AIF impaired the metastatic potential of human melanoma (A375 and SK-MEL-1) cells by upregulating cell differentiation, as assessed based on melanin content, protoporphyrin IX accumulation, and tissue transglutaminase activity [4].…”
Section: Introductionmentioning
confidence: 99%